Conservation assessment of the Drakaea livida (Orchidaceae) ecotypes and an evaluation of methods for their identification - Weinstein, Alyssa M.; Bohman, Björn; Linde, Celeste C.; Phillips, Ryan D. (Frontiers in Ecology and Evolution, 2022)
Morphologically cryptic taxa must be accounted for when quantifying biodiversity and implementing effective conservation measures. Some orchids pollinated by sexual deception of male insects contain morphologically cryptic ecotypes, such as the warty hammer orchid Drakaea livida (Orchidaceae). This species is comprised of three cryptic pollination ecotypes, which can be distinguished based on differences in pollinator species and floral volatiles. The present study aims were: a) to investigate the geographic range of the three D. livida ecotypes, enabling assessment of their conservation status; and b) to test the efficacy of different methods of identifying the D. livida ecotypes. Three methods of ecotype identification were assessed: morphometric analysis, genome size comparison, and analysis of chemical volatile composition of labellum extracts from pollinated flowers. MaxEnt species distribution models revealed that each ecotype has a different predicted geographic range, with small areas of overlap at the range margins. One ecotype is known from just ten populations over a limited geographic area, the majority of which has been cleared for agriculture and urban development. While there was broad overlap between the ecotypes in individual morphological traits, multivariate analysis of morphological traits provided correct assignment to ecotype in 87% of individuals. Using the labellum of pollinated flowers, screening for volatile chemical compounds associated with particular ecotypes returned an even higher correct assignment rate, of 96.5%. As such, we advocate that the use of volatiles from the labellum of recently pollinated flowers is an effective way to determine the ecotype of unknown individuals of D. livida, with minimal impact on the flowering plant.